THE IMAGE OF RUSSIA IN THE LANGUAGE CONSCIOUSNESS OF RUSSIAN AND CHINESE STUDENTS ACCORDING TO THE DATA OF ASSOCIATIVE EXPERIMENTS (QUANTITATIVE ANALYSIS) - A.B. Antonova; Song Luling (Многоязычие в образовательном пространстве)
The paper examines the quantitative results of free associative experiments conducted among Russian students and Chinese students studying Russian as a foreign language, with the stimulus word “Russia.” The resulting associates are ordered according to the frequency and descriptors. The most frequent ways of assigning meaning are identified, and the resulting associates are interpreted in regard to stereotypic representation. Conclusions are drawn about the structuring of the image of Russia in the linguistic picture of the world of Chinese and Russian students.